2005
DOI: 10.1017/s0950268805004565
|View full text |Cite
|
Sign up to set email alerts
|

Microbial health risk posed by table eggs in Trinidad

Abstract: A survey of the microbial quality of table eggs sold in Trinidad was conducted. For 23 poultry layer farms each visited twice approximately 1 month apart, 25 pooled eggs constituted a composite sample, for 14 shopping malls each visited twice approximately 1 month apart, six pooled eggs made a composite sample and for a total of 102 other retailers across the country each visited once over a 4-month period, six pooled eggs constituted a composite sample. Swabs of egg shells and egg content were tested for sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 23 publications
9
56
5
Order By: Relevance
“…recovered from table eggs in Denmark, with a prevalence of 2.6% [24]. Salmonella on egg shells from the local market in this study (5.3%) was also in agreement with the work of Adesiyun et al [25], who reported 5.4% Salmonella prevalence on egg shells in Trinidad. Suresh et al [26] from India also reported that the prevalence of Salmonella on egg shells was 6.1%.…”
Section: Discussionsupporting
confidence: 91%
“…recovered from table eggs in Denmark, with a prevalence of 2.6% [24]. Salmonella on egg shells from the local market in this study (5.3%) was also in agreement with the work of Adesiyun et al [25], who reported 5.4% Salmonella prevalence on egg shells in Trinidad. Suresh et al [26] from India also reported that the prevalence of Salmonella on egg shells was 6.1%.…”
Section: Discussionsupporting
confidence: 91%
“…Lower incidence was recorded on the egg shells about In the present study, the data obtained showed that E. coli was isolated from shell and yolk of Balady eggs but not from albumen (44, 0 and 22%), while lower incidence detected in Battery system which were 27.5, 9 and 19% of shell, albumin and yolk, respectively. Nearly similar results were obtained by Adesiyun et al (2005) who found this bacterium on 58.7% of shell and in 4.3% of egg contents of farm eggs also, they added that the frequency of E. coli founded in eggs depending on their rearing sources.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, the contamination rate concerning Salmonella spp. is similar to isolation rates described in other studies (1,2) and in the annual zoonosis report of the EFSA (4). Unlike Adesiyun et al (1), we found thermotolerant Campylobacter spp.…”
supporting
confidence: 91%